Physical Activity and Mental Health Patterns: Analysis of Pre-service Teacher Professional Education Students Before and During Field Experience Practice - Muhammad Dzul Fikri; Delvya Intan Kusumawardhani; Perdana Setya Prasanto; Muhammad Ilham Mauluddin (Universitas Negeri Surabaya, 2024)
Background: Professional teachers are required to have good physical and mental health. The hope is that professional teachers can carry out their daily tasks without experiencing significant fatigue. To determine changes in physical activity and mental health before and during the practice of field experiences. Methods: This research uses a quantitative approach with survey methods. The population that is the subject of the study is Pre-service PPG students of Surabaya State University (Unesa) in 2023. The instruments used involved the General Physical Activity Questionnaire (GPAQ) to assess the level of physical activity and the General Health Questionnaire (GHQ) to evaluate the level of mental health of respondents. Results: The study highlights the need to balance physical and mental health among Pre-service PPG students during field experiences. Conclusions: While physical activity increased, it wasn't statistically significant. However, slight rises in psychological distress suggest potential shifts in mental well-being, urging educational institutions to address these aspects for improved teacher education quality.